I giovani dell’Europa meridionale e gli atteggiamenti verso la democrazia: 1985-2001 - Maggini, Nicola (SocietàMutamentoPolitica, 2012)
This article aims to analyze the relationship between young people and democracy in four countries of southern Europe (Greece, Italy, Portugal, Spain) in the 1985-2001 period, using data from Eurobarometer. Attitudes towards the functioning of democracy are the focal theme of the analysis.